Trawling-induced change in benthic effect trait composition – A multiple case study - Olivier Beauchard; Clare Bradshaw; Stefan Bolam; Justin Tiano; Clément Garcia; Emil De Borger; Pascal Laffargue; Mats Blomqvist; Irini Tsikopoulou; Nadia K. Papadopoulou; Christopher J. Smith; Jolien Claes; et al. (Frontiers in Marine Science, 2023)
Introduction The importance of the response-effect trait dichotomy in marine benthic ecology has garnered recent attention. Response traits, characterising species responses to environmental variations, have been a dominant focus in the development of ecological indicators for ecosystem health assessment. In contrast, effect traits, expressing effects of organism activities on the ecosystem, still do not benefit from an equal interest in spite of the complementary facet that they provide to complete our understanding of functional diversity and ecosystem vulnerability. In this study, we explore the consequences of disturbance by bottom trawl fisheries on benthic effect trait composition. Methods To this end, we used different contexts of environmental and trawling conditions from thirteen case studies in European waters and apply the same analytical procedure to derive a gradient that solely account for trawling-induced disturbance (Partial RLQ analysis). Results Bottom trawling was found to be a selective force of benthic effect trait composition in a majority of case studies. In general, tube-dwelling species were more typical of low trawling frequencies, whereas deep burrowing species were more resistant at high trawling frequencies. Although we report significantly deleterious effects of trawling on benthic ecosystem functions, the effect trait pattern along the gradient was never related to life span, a key response trait generally assumed to express recoverability following disturbance. Furthermore, we show that trends in species multi-functionality and community functional diversity can be negative or positive along the trawling intensity gradient. Discussion We discuss the relevance of these results in light of recent developments in the framework of response and effect trait dichotomy, and provide guidelines of trait data analysis in the context of trawl fisheries impact on the sea floor. Our findings emphasize the importance of fundamental concepts from functional ecology in this context and represent a first step toward an assessment of trawling effect more oriented on benthos-mediated biogeochemical processes.